Dynamic Synergy Between Strategic Management and Augmented Reality Technology in Education System Transformation - Norliani, Norliani; Suriansyah, Ahmad; Purwanti, Ratna (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the dynamic synergy between strategic management and Augmented Reality (AR) technology in transforming the education system in the digital era. Through a comprehensive literature review, the research reveals the proven effectiveness of AR in increasing student engagement by up to 70% and enhancing conceptual understanding through immersive learning experiences. However, the adoption of AR in Indonesia faces complex challenges such as digital infrastructure gaps, policy fragmentation, and limited teacher technological readiness. Strategic management acts as a catalyst through visionary planning, resource allocation, and continuous evaluation. Key strategies include curriculum integration, teacher training, infrastructure investment, and multi-stakeholder collaboration.